Preparation of platinum-based ‘cauliflower microarrays’ for enhanced ammonia gas sensing - Hussain, G.; Aldous, L.; Silvester, Debbie (Elsevier, 2018)
© 2018 Elsevier B.V. the flux of gas to electrode surfaces determines the analytical response and detection limit. For trace concentration detection, the resulting low current prevents the miniaturisation of such sensors. Therefore, in this study, we have developed repeating arrays of nanostructures which maximise flux towards their surface. Unique platinum 3D cauliflower-shaped deposits with individual floret-shaped segments have been produced in a single step electrodeposition process. The confined walls of recessed microelectrode arrays (10 µm in diameter, 90 electrodes) are utilized to produce these structures with a high surface area. Distinct segments are observed, with the gaps corresponding to electrodes adjacent in the microarray; thus the majority of the deposits face the primary diffusion zones. The sizes and shapes of the deposits are characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM) and the largest structures are found to be 22 ± 1 µm in width and 7.9 ± 0.2 µm in height over the microhole. These modified electrodes are employed to detect ammonia using the room temperature ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [C2mim][NTf2], as an electrolyte. Current responses on the cauliflower arrays were seven times higher for linear sweep voltammetry and ca. 12 times higher for chronoamperometry, relative to the bare microrrays, and limits of detection were less than 1 part per million of ammonia (gas phase concentration). This work highlights the use of modified microarrays with highly accessible 3D structures for enhanced electroanalytical detection of analyte species at ultra low concentrations.